2009
DOI: 10.1261/rna.1371409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 8-methyladenosine as the modification catalyzed by the radical SAM methyltransferase Cfr that confers antibiotic resistance in bacteria

Abstract: The Cfr methyltransferase confers combined resistance to five different classes of antibiotics that bind to the peptidyl transferase center of bacterial ribosomes. The Cfr-mediated modification has previously been shown to occur on nucleotide A2503 of 23S rRNA and has a mass corresponding to an additional methyl group, but its specific identity and position remained to be elucidated. A novel tandem mass spectrometry approach has been developed to further characterize the Cfr-catalyzed modification. Comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
143
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 34 publications
10
143
2
3
Order By: Relevance
“…The PAB2272 protein differs from NEQ228 by the absence of the D1 domain (de Crécy-Lagard et al 2010), yet both enzymes clearly demonstrate the dual specificity, suggesting that this domain is not responsible for the dual activity of the aTrm5a proteins. Similar observations have been made for the aTrm5b-type enzyme MJ0883 (Goto-Ito et al 2008), where D1 was shown to be dispensable for the methylation of the G37 tRNA substrate. Nevertheless, one cannot exclude that the D1 domain is important at physiological temperatures above 50°C, which was used for the methylation assays during our experiments.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The PAB2272 protein differs from NEQ228 by the absence of the D1 domain (de Crécy-Lagard et al 2010), yet both enzymes clearly demonstrate the dual specificity, suggesting that this domain is not responsible for the dual activity of the aTrm5a proteins. Similar observations have been made for the aTrm5b-type enzyme MJ0883 (Goto-Ito et al 2008), where D1 was shown to be dispensable for the methylation of the G37 tRNA substrate. Nevertheless, one cannot exclude that the D1 domain is important at physiological temperatures above 50°C, which was used for the methylation assays during our experiments.…”
Section: Discussionsupporting
confidence: 79%
“…No spots corresponding to m 1 G or imG2 were detected in the absence of SSO2439 (data not shown). Since the migration profile for likely pimG2pA on TLC plates was the same as that obtained for PAB2272 and NEQ228, we concluded that the SSO2439 protein exhibits the tRNA Amino acid residues of PAB2272 that are important for the formation of m1G and imG2 derivatives A previously conducted bioinformatic analysis (de Crécy-Lagard et al 2010) in conjunction with the structural work on Methanocaldococcus jannashii Trm5b (MJ0883) and Taw2 (MJ1157) as well as Pyrococcus horikoshii PH0793 enzyme Taw2 (Goto-Ito et al 2008Umitsu et al 2009) allowed identification of several amino acid residues, critical for the recognition of the S-AdoMet cofactor and the G/imG-14 substrate at position 37 in tRNA Phe . Here, we performed the bioinformatic analysis of the archaeal Trm5a/b/c family of enzymes (Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The first is Cfr from E. coli that normally mediates the single methylation of the 8-amidine carbon of A2503 of 23S rRNA to form 8-methyadenosine (m 8 A). However, when E. coli lacks the methyltransferase RlmN that catalyzes the methylation of the 2-amidine carbon of the same A2503 in 23S rRNA, Cfr can compensate such deficiency and catalyzes the formation of doubly methylated 2,8-dimethyladenosine (m 2,8 A) (Giessing et al 2009). Similarly, a single bifunctional methyltransferase NS5 of flaviviruses catalyzes the sequential methylation of the N 7 -atom of the 5 ′ -terminal guanosine and 2 ′ -hydroxyl group of the neighboring adenosine, resulting in the formation of the type 1 cap m 7…”
Section: Discussionmentioning
confidence: 99%
“…However, at variance with the yeast Tyw1, archaeal Taw1 does not have the flavin-binding domain but contains a second Fe-S cluster instead (Perche-Letuvée et al 2012). The corresponding recombinant Taw1 enzymes of Pyrococcus horikoschii (PH1705), Methanocaldococcus jannaschii (MJ0257), and Pyrococcus abyssi (PAB2039) have been purified; and in the two last cases, their enzymatic activities have been successfully demonstrated in vitro using pyruvate as the key substrate, AdoMet as the cofactor, and dithionite as the source of reducing power (Goto-Ito et al 2007;Young and Bandarian 2011;Perche-Letuvée et al 2012).…”
Section: Biosynthesis Of Wyosine Derivatives In Archaeamentioning
confidence: 99%